Academic Journal: Revealing EFL Students' Challenges In Reading - Munawarah, Munawarah; Alfatihah, Alaiyya; Nurhaliyani, Nurhaliyani; Fatimatuzzuhroni, Siti; Jaelani, Selamet Riadi (STAI Denpasar Bali, 2023)
This study aims to identify the difficulties of reading journals for students in the English Language Education department of Hamzanwadi University. This study was analyzed using a descriptive-qualitative design. The 27 students in the fourth semester as participants by using purposive sampling. The documentation and interviews were used as instruments to collect the data. Findings show that the biggest challenges are: 1.) The students have a bad perception of academic journals; 2.) The vocabulary is too high; 3.) The sentence structure is hard to understand.